4 Using virtual reality to deliver essential neurosurgery in austere and low-resource settings. Issue 2 (23rd March 2023) - Please, H; Edemaga, D; Bolton, W; Nagadya, C; Obiga, O; Kiryabwire, J; Smith, C; Khan, M; Dhanda, J; Ekanayake, J
Abstract : Introduction: Head injuries account for >¼ of all battlefield deaths 1 . Simple but essential neurosurgical procedures on the field such as burr-holes can save lives 2, 3 . These penny-sized, manually drilled holes in the skull, enable release of compressive blood clots or placement of catheters. However, there is little to no training in this procedure for the field surgeon. As such, patients presenting in coma from traumatic head injuries are by default triaged to no treatment 1 . We provide an alternative approach, with life-saving potential- real-time guidance for field practitioners using an established virtual reality interface to enable delivery of emergency neurosurgery. Method: We carried out a combined virtual reality and face-to-face neurosurgical training program at the Human Cadaveric lab, Brighton (UK) and concurrently in Ugandan Christian University, Kampala (Uganda). We demonstrated the feasibility of remote and in-person proctorship of emergency neurosurgical procedures including burr-hole, craniotomy, and ventriculostomy, by general surgeons using non-powered neurosurgical instruments (e.g., Hudson brace, Gigli saw). Delegates had limited or no previous experience of cranial access. UK faculty worked with delegates in-person, supported by Ugandan faculty via videoconferencing. This was filmed in 360-degree video for the VRiMS (Virtual Reality in Medicine and Surgery) procedural library, accessed in real-time from Uganda, and stored for training. Results: Delegates 'attended' the teleconference via three approaches: 1.Hands-on training, Brighton, (9 delegates): UK faculty supported by picture-in-picture live-feed from Ugandan faculty. Delegates were divided into 3 groups and each performed 2 sets of burr-holes. 2.Real-time virtual reality training, Uganda, (23 delegates): low-cost cardboard headsets were provided to each delegate, used with personal smartphones to allow 360-degree video viewing. 3.Remote live-streaming (107 delegates): attendance from 19 countries. Conclusion: We demonstrate proof-of-principle for bi-directional surgical skills assessment using a remote proctorship interface combining live-streaming, 2D and 360-degree videos, and access via the VRIMS telesurgical platform.